Exploring Relationship between the Characteristics of a Region and the Effectiveness of Innovative Activities of the SME Sector in Poland - Tomasz NOREK (Communications of International Proceedings, 2020)
The main research objective of the article is to answer the question whether there is a interrelation between determinants of the region's innovativeness and the effectiveness of innovative activities carried out by the SMEs operating in the examined region. The author formulated the following hypothesis: (H1) There is a positive correlation between the determinants of innovativeness of the region and the effectiveness of innovative activities implemented by the SMEs operating in the region. In the study, an exploratory-descriptive method was used, involving a statistical aggregation of obtained results in selected analytical sections. The survey covered 1920 enterprises from all regions of Poland. The data necessary to assess the effectiveness of innovation processes of the surveyed entities were collected by means of an online survey. The study was carried out in the period from June 2019 to September 2019. Moreover, the data published by EUROSTAT and the Polish Central Statistical Office concerning innovation in Polish regions were used. The completed study confirmed the research hypothesis – regional determinants significantly influence the effects of innovative activities. The effectiveness of implemented innovation processes is higher in the surveyed SMEs operating in regions with greater innovative potential.